2014
DOI: 10.1007/s00246-014-0961-z
|View full text |Cite
|
Sign up to set email alerts
|

Parental Mental Health Moderates the Efficacy of Exercise Training on Health-Related Quality of Life in Adolescents with Congenital Heart Disease

Abstract: To evaluate the moderating influence of parental variables on changes in health-related quality of life (HRQoL) in adolescents with Tetralogy of Fallot (ToF) or a Fontan circulation after participation in standardized exercise training. A multicenter randomized controlled trail in which 56 patients, aged 10-15, were randomly allocated (stratified by age, gender, and congenital heart disease) to a 12-week period with either: (a) 3 times per week standardized exercise training or (b) care-as-usual (randomization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
12
0
3
Order By: Relevance
“…Numerous studies have demonstrated that youth with CHD, including the Fontan population, have suboptimal physical activity levels, falling short of existing recommendations. 4,[30][31][32] This reduced physical activity may be due in part to restrictions imposed by the child's cardiologist, parents, teachers/coaches, and/or themselves, [33][34][35] as well as numerous perceived barriers by the youth themselves. 5,[36][37][38] Fortunately, clinical recommendations have shifted from one of activity restriction to activity promotion in the CHD population.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that youth with CHD, including the Fontan population, have suboptimal physical activity levels, falling short of existing recommendations. 4,[30][31][32] This reduced physical activity may be due in part to restrictions imposed by the child's cardiologist, parents, teachers/coaches, and/or themselves, [33][34][35] as well as numerous perceived barriers by the youth themselves. 5,[36][37][38] Fortunately, clinical recommendations have shifted from one of activity restriction to activity promotion in the CHD population.…”
Section: Discussionmentioning
confidence: 99%
“…49 To this end, in a recent study, it was stressed that parental mental status had a direct impact on the level of physical activity of children with CHD. 42 Goldbeck and Melches 3 proposed that clinicians should take into account the limited ability of caregivers to recognise the patients' subjective health perception, mainly in less directly observable domains of well-being and functioning.…”
Section: Discussionmentioning
confidence: 99%
“…50 Moreover, depressive mood seems to have a positive correlation with lower physical and psycho-social quality of life. 42 This is more obvious during adolescence, as depressive symptoms and loneliness affected negatively the quality of life in adolescents with CHD. 45 In general, children with CHD may face significant internalising, externalising, and attention problems compared with the healthy population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations